Korpusbasierte Untersuchung der Wortbildungsaffixe im Luxemburgischen. Technische Herausforderungen und linguistische Analyse am Beispiel der Produktivität - Joshgun Sirajzade (Zeitschrift für Wortbildung)
The project WBLUX (Wortbildung des moselfränkisch-luxemburgischen Raumes) at the University of Luxembourg aims at the investigation of Luxembourgish word formation through different text sorts and genres. In order to achieve this goal the compilation of an annotated corpus is needed. This article gives an example for benefits of using a corpus with annotations like parts of speech, lemmata and word formation affixes in the analysis of productivity of some selected word formation affixes of Luxembourgish. Then it describes how one can achieve such a corpus from a technical point of view. This includes the choice of corpus format, of a database platform and the designing of programs needed for the annotation process of word formation itself. This article also suggests new corpus linguistic approaches for research of word formation like analyzing the usage of word formation bases in the entire corpus or performing context analysis in order to determine semantical functions of each suffix.